1995
DOI: 10.1259/dmfr.24.3.8617388
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stroke-prone patients by panoramic and cervical spine radiography.

Abstract: Panoramic radiographs obtained during the course of routine dental treatment may demonstrate calcified carotid atheromas in patients at risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 14 publications
1
15
1
5
Order By: Relevance
“…1,2 Specifically, stroke is the third aetiology of death in the USA today, preceded only by cardiovascular disease and cancer. 3,4 Atherosclerosis is believed to be responsible for approximately 50% of all embolic strokes in the USA and is accountable for billions of dollars in direct and indirect costs annually. 5 Not only in the USA, but also in other countries, atherosclerosis and its more dramatic consequences of stroke and heart attack, represent an important health problem.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Specifically, stroke is the third aetiology of death in the USA today, preceded only by cardiovascular disease and cancer. 3,4 Atherosclerosis is believed to be responsible for approximately 50% of all embolic strokes in the USA and is accountable for billions of dollars in direct and indirect costs annually. 5 Not only in the USA, but also in other countries, atherosclerosis and its more dramatic consequences of stroke and heart attack, represent an important health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the incidence of carotid artery calcification, Friedlander et al reported that carotid artery calcification was observed in six of 134 outpatients aged 65 years or older (mean age, 68.2 years; incidence, 4.5 %) 2) , and that, in another study of 304 outpatients aged 55 years or older without any past morbidity, carotid artery calcification was observed in 10 outpatients (approximately 3 %) 6) . In a clinical study conducted in 1195 patients with carotid artery calcification by Sato et al 7) , findings suggestive of carotid artery calcification were detected on panoramic radiographs in 48 patients (4.0 %), who were 50 years or older with a mean age of 70.3 years.…”
Section: Discussionmentioning
confidence: 98%
“…Digital tomosynthesis (DTS) is currently considered in clinic as a standard or the next-generation X-ray imaging modality since it yields a three-dimensional (3D) image with imaging doses comparable to conventional radiography [1][2][3][4][5]. In current DTS, the X-ray source typically moves along a line segments or a circular arc set in a longitudinal plane around the object during the projection acquisition, and a computationally-efficient filtered-backprojection (FBP) method is often used for image reconstruction.…”
Section: Introductionmentioning
confidence: 99%